2015
DOI: 10.11646/zootaxa.3946.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Ngirhaphium Evenhuis & Grootaert from southern Thailand (Diptera: Dolichopodidae) with the description of a new species

Abstract: The genus Ngirhaphium Evenhuis & Grootaert, 2002 is reported for the first time from Thailand in particular from mangroves on the coast of the Andaman Sea in southern Thailand. Three species were found: N. murphyi Evenhuis & Grootaert, 2002, N. sivasothii Grootaert & Puniamoorthy, 2014 and N. chutamasae sp. nov. The latter species is described and illustrated and a key to all four known species is provided. COI barcode data showed that the new species is most closely related to N. murphyi with a genetic distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Thinophilus in Southeast Asia thrives in marine habitats (Grootaert & Meuffels 2001;Evenhuis & Grootaert 2002;Samoh et al 2015Samoh et al , 2017Grootaert 2018), where they are often found on rocky shores, but most species are found in front mangroves or follow the creeks inside the mangrove. A few species are non-marine, such as T. mekongensis Grootaert, 2017, and the very common and widespread T. nitens Grootaert & Meuffels, 2001 and T. setiventris Grootaert & Meuffels, 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Thinophilus in Southeast Asia thrives in marine habitats (Grootaert & Meuffels 2001;Evenhuis & Grootaert 2002;Samoh et al 2015Samoh et al , 2017Grootaert 2018), where they are often found on rocky shores, but most species are found in front mangroves or follow the creeks inside the mangrove. A few species are non-marine, such as T. mekongensis Grootaert, 2017, and the very common and widespread T. nitens Grootaert & Meuffels, 2001 and T. setiventris Grootaert & Meuffels, 2001.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous survey (Grootaert & Meuffels 2001) 15 species belonging to seven genera of Dolichopodidae were found. Samoh et al (2015) added the genus Ngirhaphium Evenhuis & Grootaert, 2002 with three species, resulting in 18 known species from southern Thailand to date. Only three species of Thinophilus have been recorded from peninsular Thailand until now: T. nitens Grootaert & Meuffels, 2001, T. parmatus Grootaert & Meuffels, 2001 and T. setiventris Grootaert & Meuffels, 2001.…”
Section: Introductionmentioning
confidence: 99%